2018
DOI: 10.17576/jsm-2018-4711-05
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Field Soil Drought Stress on Some Key Physiological, Yield and Quality Traits of Selected Newly-Developed Hexaploid Bread Wheat (Triticum aestivum L.) Cultivars

Abstract: Drought is one of the commonly occurring environmental stresses, limiting crop production in many countries. Selection of cultivar is the most effective and economical means for alleviating the adverse effects of drought stress on crops. The present study aimed to investigate the growth, some physiological processes, yield and quality of some newly-developed wheat cultivars (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
(46 reference statements)
1
2
0
Order By: Relevance
“…In addition to grain yield, variation in quality traits such as protein content, Zeleny sedimentation and falling number under drought conditions are also reported (Bella et al, 2011). Increasing protein content of wheat grains under limited water conditions has been previously reported by several studies (Gooding et al, 2003;Shahzad et al, 2018;Barutcular et al, 2016). However, drought effect on Zeleny sedimentation value, for instance, is still not clear.…”
Section: Introductionsupporting
confidence: 62%
“…In addition to grain yield, variation in quality traits such as protein content, Zeleny sedimentation and falling number under drought conditions are also reported (Bella et al, 2011). Increasing protein content of wheat grains under limited water conditions has been previously reported by several studies (Gooding et al, 2003;Shahzad et al, 2018;Barutcular et al, 2016). However, drought effect on Zeleny sedimentation value, for instance, is still not clear.…”
Section: Introductionsupporting
confidence: 62%
“…Many researchers have suggested that there is a significant potential to increase agricultural productivity with a considerable increase in the rainwater use efficiency, particularly in rain-fed areas where crops depend only on rainfall [17,20,21]. Although the ridge-furrow mulching technique is considered very beneficial for achieving enhanced yield in rain-fed agriculture [22][23][24], there is still a need to understand the capture and utilization of rainwater under different mulches for clarifying physiological progression, growth and development of the crop. In general, crops are planted on the ridge in a ridge-furrow system that received little advantage from rain as rainwater makes a channel into the furrow areas, especially in the case of a light shower.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that elevated CO 2 causes a 20–30% increase in net assimilation rate, together with an increase in dry matter and yield of crops (Cruz et al, 2018; Pan et al, 2018; Xie et al, 2018). Rising levels of CO 2 , temperature and water‐deficit cause promising effects on plant growth and production, as the potential beneficial effects of elevated CO 2 include optimal growth yield in areas where drought currently causes crop failure (Shahzad et al, 2018; Wasaya et al, 2021). According to AbdElgawad et al (2015), elevated CO 2 has been shown to mitigate the stress impact of drought, and they quote examples of how the reduction in drought stress affects barley and alfalfa crops (Robredo et al, 2007; Zeid and Shedeed, 2006).…”
Section: Introductionmentioning
confidence: 99%